Implementation of Aceh Health Insurance (Jaminan Kesehatan Aceh) 2013–2021: Has health equity been achieved for all Acehnese after armed conflict? - Yani, Muhammad; Ruby, Mahlil; Puspandari, Diah A.; Munawar, Munawar; Fachrurrozi, Kamal; Candra, Aditya; Ilzana, Teuku M.; Khaled, Teuku M.; Rahmi, Cut R. (Narra J, 2023)
Aceh Health Insurance (Jaminan Kesehatan Aceh—JKA) has been implemented since 2010 to increase the health equity by covering the health expenses and guaranteeing that all Acehnese are covered regardless of their economic, educational, and social statuses. However, since its implementation, there has been no study on its impact on health quality, particularly regarding the utilization of the main referral hospital (Dr Zainoel Abidin Hospital located in Banda Aceh) and the effects of the geographic accessibility and the number of specialist doctors in each regency/city on hospital utilization. This retrospective study assessed the equity factors during the Aceh Health Insurance implementation and during its integration to National Health Insurance (Jaminan Kesehatan Nasional—JKN) from 2013 to 2021 using data of travel time (time spent for travelling from the origin regency/city of referred patients to the main referral center) and healthcare resources (number of specialist doctors). The data were analyzed using Student’s t-tests, Kolmogorov-Smirnov or Mann-Whitney U test when appropriate. Williamson Index was calculated to determine the disparities of health equity between regencies. Our data indicated the noticeably increase of health facilities utilization since the implantation of Aceh Health Insurance. However, there was no equity in the use of main referral facility by the residents in Aceh - was dominated by residents who lived closer and from more populated regencies/cities. In conclusion, there are accessibility and financial hardship barriers in accessing the health care facilities during the implementation of Aceh Health Insurance that need to be addressed by the government to achieve the health equity for all Acehnese.